THE IMPORTANCE OF THE USE OF TECHNOLOGIES IN TEACHING READING SKILL TO ENGLISH LEARNERS - Jamalova, Dilafruz (Журнал иностранных языков и лингвистики, 2023)
English language is one of widely used languages all over the world and interest in learning the language has been increasing over the years. Reading is one of indispensable language skills and there are a number of efficacious methods that can be used in teaching reading in EFL classes. The wide availability of technologies and internet resources can be a really worthwhile support in the educational field, besides technology provides opportunity to interact with students online. This article discusses the essence of the usage of technologies in the improvement of reading comprehension.